Deoxycholic Acid Triggers NLRP3 Inflammasome Activation and Aggravates DSS-Induced Colitis in Mice - Zhao, Shengnan; Gong, Zizhen; Zhou, Jiefei; Tian, Chunyan; Gao, Yanhong; Xu, Congfeng; Chen, Yingwei; Cai, Wei; Wu, Jin (Frontiers in Immunology, 2016)
A westernized high-fat diet (HFD) is associated with the development of inflammatory bowel disease (IBD). High level fecal deoxycholic acid (DCA) caused by HFD contributes to the colonic inflammatory injury of IBD, however, the mechanism concerning the initiation of inflammatory response by DCA remains unclear. In this study, we sought to investigate the role and mechanism of DCA in the induction of inflammation via promoting NLRP3 inflammasome activation. Here we for the first time showed that DCA dose-dependently induced NLRP3 inflammasome activation and highly pro-inflammatory cytokine-IL-1β production in macrophages. Mechanistically, DCA triggered NLRP3 inflammasome activation by promoting cathepsin B release at least partially through sphingosine-1-phosphate receptor 2 (S1PR2). Colorectal instillation of DCA significantly increased mature IL-1β level in colonic tissue and exacerbated DSS-induced colitis, while in vivo blockage of NLRP3 inflammasome or macrophage depletion dramatically reduced the mature IL-1β production and ameliorated the aggravated inflammatory injury imposed by DCA. Thus, our findings show that high level fecal DCA may serve as an endogenous danger signal to activate NLRP3 inflammasome and contributes to HFD-related colonic inflammation. NLRP3 inflammasome may represent a new potential therapeutical target for treatment of IBD.